Exploration of genetic diversity of Plasmodium vivax circumsporozoite protein (Pvcsp) and Plasmodium vivax sexual stage antigen (Pvs25) among North Indian isolates - Hargobinder Kaur (5821277) (2019)
Malaria is one of the important vector-borne diseases with high fatality rates in tropical countries. The pattern of emergence and spread of novel antigenic variants, leading to escape of vaccine-induced immunity might be factors responsible for severe malaria. A high level of polymorphism has been reported among malarial antigens which are under selection pressure imposed by host immunity. There are limited reports available on comparative stage-specific genetic diversity among Plasmodium vivax candidate genes in complicated vivax malaria. The present study was planned to study genetic diversity (Pvcsp and Pvs25) among complicated and uncomplicated P. vivax isolates. Pvcsp and Pvs2-specific PCRs and DNA sequencing were performed on P. vivax PCR positive samples. Genetic diversity was analysed using appropriate software. The present study was carried out on 143 P. vivax clinical isolates, collected from Postgraduate Institute of Medical Education and Research, Chandigarh. Among the classic and variant types of Pvcsp, the VK210 (99%; 115/116) was found to be predominant in both complicated and uncomplicated group isolates. Out of the various peptide repeat motifs (PRMs) observed, GDRADGQPA (PRM1) and GDRAAGQPA (PRM2) was the most widely distributed among the P. vivax isolates. Whereas among the Pvs25 isolates, 100% of double mutants (E97Q/I130T) in both the complicated (45/45) as well as in the uncomplicated (81/81) group was observed. An analysis of genetic variability enables an understanding of the role of genetic variants in severe vivax malaria. Other Information Published in: Malaria Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s12936-019-2939-z